Back Cover: Electronic structure of formamidinium ions in lead triiodide perovskites (Phys. Status Solidi RRL 9/2016). Issue 9 (September 2016) - Shen, Pengfei; Nie, Kaiqi; Sun, Xuhui; Liu, Lijia; McLeod, John A.
Abstract : No abstract is available for this article. Abstract : Perovskite formamidinium lead triiodide (FAPbI3 ) is a very promising photovoltaic material. Unfortunately, under ambient or even vacuum conditions perovskite FAPbI3 slowly but spontaneously converts to a hexagonal phase. This hexagonal phase has a much larger band gap and is unsuitable for photovoltaics. To elucidate the mechanism behind this phase change, Pengfei Shen et al. (pp. 677–681 ) study the electronic structure of both perovskite and hexagonal FAPbI3 films using soft X‐ray absorption near edge structure (XANES) and density functional theory. The authors find that the C and N 2p states of the formamidinium ions (FA) hybridize with the Pb, I lattice states at the conduction band minimum (CBM) in hexagonal, but not perovskite, FAPbI3 . The driving influence in the phase change may be related to increased hydrogen bonding with the I in the lattice. The authors also find that due to the core–hole shift, the onset of the C K‐edge XANES is aligned with the valence band maximum (VBM). C K‐edge XANES is therefore a useful probe for investigating shifts in the valence band in other organic–inorganic hybrid perovskites.